Analysis of Requirements for Virtual Laboratory Interactive Multimedia for Class X Electrical Conductivity - Herlika Herlika (CV Media Inti Teknologi, 2022)
This study aims to analyze the needs of virtual laboratory interactive multimedia. This analysis is the initial stage of the ADDIE development model. The method used by researchers is descriptive. Researchers will describe the data obtained about the needs of interactive multimedia virtual chemistry laboratories in Bengkulu City High School. At this stage of the analysis, an initial problem analysis was carried out through the results of interviews with class X chemistry teachers and through filling out student needs questionnaires to X MIPA class students at SMA Negeri 4, SMA Negeri 6, SMA Negeri 7 Bengkulu City. The next stage is analyzing the curriculum, materials and students from the results of interviews and filling out questionnaires by students. Based on the results of the research that has been conducted, the researcher can conclude that: (1) students sometimes feel bored with the media used by the teacher; (2) Teachers have not utilized varied media; (3) Teachers and students need interesting media to make it easy to understand chemistry lessons during the learning process; (4) The practicum of electrical conductivity is not able to explain the ionization reaction that occurs; (5) Teachers need a virtual laboratory interactive multimedia on electrical conductivity material as an alternative solution to improve learning outcomes and motivation in the chemistry learning process.